Tax Literacy for SMEs to Students’on Universitas Tekhnologi Mara, Malaysia - Fuadah, Luk Luk; Wahyudi, Tertiarto; Muktarudin, Muktarudin; Andriana, Isni; Kalsum, Umi; Safitri, Rika Henda; Novelia, Rizka; Arisman, Anton (Jurnal Pengabdian Masyarakat (ABDIRA), 2025)
This Community Service is held with the Accounting Research Institute (ARI) of Universitas Tekhnologi MARA (UiTM), Malaysia. The primary goal of this service is that participants are expected to understand taxation for Small and Medium Enterprises in Indonesia. Participants can also understand taxation in Indonesia, especially for Small and Medium Enterprises so that it can be compared with the conditions in Malaysia. The method used in the discussion of tax literacy for small and medium enterprises is online, namely via zoom. It was implemented on October 25, 2024, which was held at 7:30 WIB where there was a 1 hour difference with Malaysia, namely 08:30. This activity was carried out using zoom online which was attended by 3 classes chaired by Dr. Muhammad Nazmul Hoque from the Faculty of Accountancy, Universitas Teknologi Mara, Malaysia. At the time of zoom, not only students from Malaysia, but also students from Indonesia with the resource person being Prof. Dr. Luk Luk Fuadah, SE., MBA., Ak., CA. Contributions for ARI UiTM Students include Improving Practical Tax Knowledge, Strengthening Soft Skills, Field Experience, Understanding Tax in a Social Context, Strengthening the Role as an Agent of Change.